Out-of-pocket costs and other determinants of access to healthcare for children with febrile illnesses: a case-control study in rural Tanzania. - Joëlle Castellani; Borislava Mihaylova; Silvia M A A Evers; Aggie T G Paulus; Zakayo E Mrango; Omari Kimbute; Joseph P Shishira; Francis Mulokozi; Max Petzold; Jan Singlovic; Melba Gomes (PLoS ONE)
Objectives To study private costs and other determinants of access to healthcare for childhood fevers in rural Tanzania. Methods A case-control study was conducted in Tanzania to establish factors that determine access to a health facility in acute febrile illnesses in children less than 5 years of age. Carers of eligible children were interviewed in the community; cases were represented by patients who went to a facility and controls by those who did not. A Household Wealth Index was estimated using principal components analysis. A multivariable logistic regression analysis was performed to understand the factors which influenced attendance of healthcare facility including severity of the illness and household wealth/socio-demographic indicators. To complement the data on costs from community interviews, a hospital-based study obtained details of private expenditures for hospitalised children under the age of 5. Results Severe febrile illness is strongly associated with health facility attendance (OR: 35.76, 95%CI: 3.68-347.43, p = 0.002 compared with less severe febrile illness). Overall, the private costs of an illness for patients who went to a hospital were six times larger than private costs of controls ($5.68 vs. $0.90, p<0.0001). Household wealth was not significantly correlated with total costs incurred. The separate hospital based cost study indicated that private costs were three times greater for admissions at the mission versus public hospital: $13.68 mission vs. $4.47 public hospital (difference $ 9.21 (95% CI: 7.89 -10.52), p<0.0001). In both locations, approximately 50% of the cost was determined by the duration of admission, with each day in hospital increasing private costs by about 12% (95% CI: 5% - 21%). Conclusion The more severely ill a child, the higher the probability of attending hospital. We did not find association between household wealth and attending a health facility; nor was there an association between household wealth and private cost.